Cardioprotective Mechanisms of Hibiscus sabdariffa Anthocyanins Against Myocardial Ischaemia–Reperfusion Injury via the PI3K/Akt Pathway - Rachmat Hidayat; Abhimanyu Putra (HM Publisher, 2026)
Myocardial ischaemia–reperfusion (I/R) injury contributes up to 50% of the final infarct size after primary percutaneous coronary intervention (PCI) in ST-elevation myocardial infarction, yet pharmacological cardioprotection in the clinic remains elusive. Hibiscus sabdariffa L. (Malvaceae), known in Indonesia as rosella, is rich in delphinidin-3-O-sambubioside (D3S) and cyanidin-3-O-sambubioside (C3S) anthocyanins. This study determined whether an HPLC-DAD–standardised anthocyanin-rich H. sabdariffa calyx extract (HSE) protects rat myocardium from I/R injury through formal PI3K/Akt activation. Sprague–Dawley rats (n = 48; six arms of n = 8) were randomised to sham, I/R control, HSE 100, 200 or 400 mg/kg/day p.o. for 14 days, or HSE 200 mg/kg + LY294002 (PI3K inhibitor); rats underwent 30-min LAD occlusion plus 120-min reperfusion. H9c2 cardiomyoblasts underwent 6-h hypoxia plus 12-h reoxygenation. HSE 200 mg/kg reduced infarct size from 41.8% to 18.4% of area at risk (F(5, 42) = 98.4, p < 0.001, partial η² = 0.92), lowered serum cTnI from 8.42 to 2.96 ng/mL (p < 0.001), and increased p-Akt(Ser473) 3.4-fold and the Bcl-2/Bax ratio 5.6-fold. D3S docked PI3K-p110α at ΔG = −9.2 kcal/mol. LY294002 abolished cardioprotection, formally proving PI3K/Akt-dependence. H. sabdariffa anthocyanins exert PI3K/Akt-mediated cardioprotection against myocardial I/R injury, supporting their development as Indonesian phytotherapeutic adjuncts for elective PCI.